Museum-making in Vietnam, Laos, and Cambodia : cultural institutions and policies from colonial to post-colonial times - Paquette, Jonathan (New York : Routledge, 2022)
"Building on archival work undertaken in France and fieldwork undertaken in Southeast Asia, Museum-Making in Vietnam, Laos, and Cambodia provides a critical analysis of museum histories and development in three former colonial territories. This work documents the development of museums in French Indochina (1862-1954), specifically Vietnam, Laos, and Cambodia. The book explores the colonial culture of exhibition, traces the growth of museum collections through archaeological missions to Indochina and other parts of Asia, and examines the role of museums in the cultural life of this colonial society. In particular, the author re-contextualizes the role and part played by colonial museums in the implementation of heritage policies during the colonial era in French Indochina, a dimension that is often overlooked. Additionally, the book addresses the effects that the Second World War, the Vichy Regime, and the Japanese occupation had on these cultural institutions. The transformation of these museums in post-independence Vietnam, Laos, and Cambodia is also discussed. Providing comparisons with other colonial and post-colonial experiences, Museum-Making in Vietnam, Laos, and Cambodia will be a valuable resource for researchers in museum and heritage studies. It will also appeal to researchers and graduate students engaged in the study of history, anthropology, sociology, political science, and development and international studies"--
Introduction -- French Indochina as a colonial project -- Museum-making in French Indochina -- Heritage preservation and museum administration in a colonial society -- Collection development and collection management -- Museums and their publics -- Museums in post-colonial times -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Museums -- Indochina -- Administration -- History; Museums -- Political aspects -- Indochina -- History; Museums -- Social aspects -- Indochina -- History; Historic preservation -- Indochina -- History; Indochina -- Colonia influence; France -- Colonies -- Asia -- Administration -- History; HISTORY / Asia / Southeast Asia